Evaluation of safety and health performance on construction sites (Kuala Lumpur). - Yakubu, D. M.; Ishak, Mohd. Bakri (Canadian Center of Science and Education, 2013)
Occupational safety and health Act (Act 514) obligate each employer to provide and maintain a safe and healthful workplace for all his employees. Construction is a risky business with a lot of injuries and illness, due to poor safety performances. The aim of the study is to investigate the safety and health performance of contractors on construction sites. A comparative and sensitivity analysis conducted reveal that as allocation to the construction increases so also the rate of accidents increases and that fatal accidents contribute more to the total accidents rates, as such there is need to assess the performance of contractors as regard to safety and health operation. The result of the SHASSIC score reveal that the sites consider for the study were 3 – star in ranking, were its risks/hazards activities are well managed and documented, but still there are other risks/hazards activities that are not taken care off due to negligent on the side of the contractors. The finding affirm the importance of safety program in construction site, as such to ensure successful implementation of the safety program, the following condition must be made; management commitment, safe work condition and safe work habit.